Effects of Nitrogen and Phosphorus Fertilizer on Growth and Yield of Dragon Fruit (Hylocereus polyrhizus) - Bambang Hariyanto; Eliza Mayura; Irwan Muas; Jumjunidang Jumjunidang; Liza Octriana (Green Engineering Society, 2023)
Nitrogen and Phosphorus fertilizers are required to enhance the plant growth and yield. The appropriate nitrogen and phosphorus doses on the growth and yield of dragon fruit (Hylocereus polyrhizus) are not well known. A study to evaluate the effect of nitrogen and phosphorus fertilizers on the growth and yield of dragon fruit (Hylocereus polyrhizus) was arranged in a completely randomized block design with two factors and three replications. The treatments consisted of four nitrogen doses (0, 50, 75 and 100 g-1pillar) and four phosphorus doses (0, 50, 75 and 100 g-1pillar). Growth and yield were significantly (p < 0.01) affected by increasing nitrogen and phosphorus doses and showed interaction on the number of shoots, number of flowers, and fruit sets. The number of shoots increased from around 102.98 to 162.10 % at nitrogen dose 100 g and phosphorus doses 50, 75 and 100 g compared with no treatment. Nitrogen dose at 100 g and phosphorus dose at 100 g produced 152.64 % more number of flowers compared to 0 g phosphorus. The fruit set increased by 58.32% at dose of 50 g nitrogen and 50 g phosphorus. Nitrogen applied at 100 g compared with 0 g nitrogen and phosphorus at different phosphorus doses increased in the number of fruits were 139.35 % and 13.56 - 58.15 %. Individual fruit weight among nitrogen doses and TSS among nitrogen and phosphorus doses showed no significant difference. Application of nitrogen fertilizer at 50 g-1pillar and phosphorus at 75 g-1pillar produced maximum yield, respectively, and thus, it should be recommended as optimum doses.